SENSITIVITAS EKSTRAK DAUN Xylocarpus sp. TERHADAP BAKTERI Pseudomonas sp. - Putri, Atika; Syawal, Henni; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from November 2016 until April 2017 in the Parasites and Fish Disease Laboratory, Faculty of Fisheries and Marine, University of Riau and Integrated Chemical Laboratory, Faculty of Mathematics and Natural Science of Health Muhammadiyah University of Riau. The aims of this research was to determine the sensitivity of Xylocarpus sp. leaf extract on Pseudomonas sp., the range of Minimum Inhibitory Concentration (MIC) of Xylocarpus sp. leaf extract can inhibit the growth of Pseudomonas sp. and know the toxicity of Xylocarpus sp. leaf extract against African catfish, the LC50 test conducted by immersion for 24 hours. This research used an experimental method. The treatment that being used were giving Xylocarpus sp. leaf extract at a concentration of D1 (100%), D2 (90%), D3 (80%), D4 (70%), D5 (60%), D6 (50%), D7 (40%), D8 (30%), D9 (20%), D10 (10%) and Kp : control (cloramphenicol). The results showed showed that Xylocarpus sp. leaf extract can inhibit the growth of Pseudomonas sp. at a concentration of 10% with an average of 8,12 mm zone of inhibition. MIC test showed a concentration of 8,5% average number of colonies of bacteria as much as 248,67 × 108CFU/mL can inhibit the growth of Pseudomonas sp. LC50 Xylocarpus sp. leaf extract against African catfish by immersion for 24 hours in the concentration 8,6% (860 ppm).Key words : Xylocarpus sp., Minimum Inhibitory Concentration, Pseudomonas sp., Sensitivitas, LC50